2021
DOI: 10.1002/aenm.202101530
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Porous Polymers: Ground‐Breaking Materials for Solar Energy Conversion

Abstract: poor applicability for movable applications. Therefore, the development of new technologies to store renewable energy is really important to achieve the transition to a greener energy system. [3] Although new battery technologies will likely meet the need for cost-effective energy storage (1-3 days) for short time scales, fuels are the only effective option for longerterm, seasonal storage, and long-distance transportation applications. [4] Collecting and loading solar energy into electric power and more inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 223 publications
(308 reference statements)
0
53
0
Order By: Relevance
“…[ 9–11 ] In particular, significant advances in the preparation of conjugated microporous polymer (CMP) photocatalysts with high photocatalytic activity have been achieved. [ 12–14 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9–11 ] In particular, significant advances in the preparation of conjugated microporous polymer (CMP) photocatalysts with high photocatalytic activity have been achieved. [ 12–14 ]…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] In particular, significant advances in the preparation of conjugated microporous polymer (CMP) photocatalysts with high photocatalytic activity have been achieved. [12][13][14] Many studies revealed that designing a donor-acceptor (D-A) molecular structure is an efficient strategy to boost the photocatalytic activity of conjugated polymer photocatalysts, [15][16][17][18] since the intrinsic electron push-pull effect in a D-A conjugated polymer could promote the separation of light-induced hole/ electron. The nature of electron donor and acceptor units plays a key point in the charges transfer and separation, which affect significantly the photocatalytic activity.…”
mentioning
confidence: 99%
“…They have attracted especially high interest in recent years due to the significant developments in the synthetic approaches and desired applications [ 2 , 3 , 4 ]. Taking into account the favorable processability of conductive polymers, possibility of tailoring their structures and functions at the molecular scale, low production costs, and reasonable stability, π-conjugated polymers may find applications in next-generation electronic devices [ 5 ], such as photovoltaic organic solar cells [ 6 ], bioelectronics [ 7 ], energy storage devices [ 8 ], energy conversion systems [ 9 ], and electrochemical transistors [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To test the feasibility of constructing CMP skeletons composed of only aza-fused rings by deploying starting materials without the constraint of steric hindrance, homocoupling of easily available monomers (e.g., aromatic halides) with pyridine (Py), bipyridine (Bipy), and phenanthroline (Phen) cores are preferred, considering the wide application and attractive performance of nanoporous materials containing these functionalities in the field of separation, catalysis, and energy storage. [5,12,15,[20][21][22][23][24] However, their linear structures make it difficult to generate polymer networks with permanent porosity. We envisaged that we could leverage the coordination ability of these organic ligands with metal species to realize in situ formation of units with high steric hindrance and multiple reactive sites, which, after the polymerization process, can be disintegrated without disturbing the as-formed polymer architecture.…”
Section: Resultsmentioning
confidence: 99%